Characteristic of Pumpkin Powder (Cucurbita moschata) - Sri Usmiati; D Setyaningsih; E Y Purwani; S Yuliani; Maria O G (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Instant powder of pumpkins was made by mollen dryer in order to extend the product shelf life The aim of the research was to determine the characteristics of the pumpkin powder. The research had been designed using completely randomized block factorial pattern, two levels of drying-up temperature and three levels of mollen dryer speed rotation on two blocks of pumpkin (I and II groups). The parameters measured were percentage of yield, water content, ash, solubility, and sugar, pH, bulk density (g/ml), beta-carotene (µg/g), colors, and hedonic test (scale 1 = not accepted through 5 = really accepted). The research result showed that the drying temperature affected solubility, and the speed rotation affected sugar content of pumpkin powder. The best pumpkin powder was produced by mollen dryer at 60ºC degree and 6 rpm speed rotation which was characterized by high yield and solubility, also produced best hedonic value on taste, color and performance as compared to the other treatment. Key words : Pumpkin, drying-up temperature, speed rotation, mollen dryer